Foucault’s Empire of the Free - Richard Alston (Foucault Studies, 2017)
This essay argues that the engagement with Greece and Rome after The Will to Knowledge allowed Foucault to bring clarity to his conception of limited freedom in complex societies. The Classical fulfilled this function paradoxically by being jarringly different from and integral to the discourses of modern sexuality. Foucault’s engagement with the Classical in The Use of Pleasure and The Care of the Self continued his established method of uncovering the development of a discourse, or set of discourses, over time. He thereby demonstrated the historical specificity of understandings of sexuality and the self. It follows that if the ancient self was a historical construct, then the modern self must also be such. But Foucault’s Classical engagement leads him to an innovative position in which the disciplinary dynamics of ancient self-knowledge offer a practical philosophy. Foucault’s Greek philosophy could have effects through two related mechanisms: the care of the self through askesis (discipline) and the speaking of truth to power through parresia (free speech). Through the rigors of askesis, the self can be rendered an object of analysis and hence a critical position external to the self can be achieved. Externality allows the philosopher to exercise parresia since the constraints of society have been surpassed and consequently offers a prospect of agency and a measure of freedom. The second part of the essay questions the extent of that freedom by reading Foucault against Tacitus, particularly the Agricola and the mutinies episode in the Annales. These episodes show the limitations of parresia and how parresia is bound into the workings of imperial power (and not a position external to that power). In the Tacitean model, externality is a viable political stance (achieved by Agricola), but is problematic ethically. The essay concludes by contrasting Foucauldian and Tacitean models of historical change.